Setting standard levels for some physical requirements in order to select young football talents. (Field study on the two teams of N Magra and ES Setif for 14 years - Saadaoui , Fayssal; BRIKI , Tahar (sports creativity, 2025)
The researcher discussed the evaluation of the criteria approved by the Algerian clubs in the process of selecting young talents in football and conducted an exploratory study in the light of this by offering some tests for the selection process to the specialists and then conducting the exploratory experiment on a sample of 10 players and then the main study on a sample consisting of 53 players from the ES Setif and Magra team teams ranged in age from 14-15 years, and given the nature of the topic, we used the appropriate descriptive approach for